Avaliação da efetividade do sítio da Receita Federal na internet: um referencial para práticas de e-Gov - Rampelotto, Alexandre (2013)
T his dissertation introduces the topic e-Gov, its introduction as public policy in Brazil and use as an instrument for interaction with citizens. With theoretical studies on electronic government and key points for the evaluation of government websites and portals, this work aimed to evaluate the effectiveness of the Federal Revenue website in information and services supply to citizens. References to the Federal Revenue of Brazil as a major agency in the use of new information and communication technologies result in a high number of online consultations conducted, contrasting with the significant number of face-to-face consultations for services that are available at Internet, pointed out by statistics on agency. Findings justifying the choice of the Federal Revenue as an object of study and characterize this work as a case study. Through a multimethod model an evaluation instrument was validated, and reapplied in the researched population to effectively evaluate the Federal Revenue website as proposed in the main objective of this work. At the same time, another instrument was validated and applied during the face-to-face service to find reasons to search this way. Was traced a profile of users of information and services and identified the factors that contribute to the effectiveness of the website or that lead people to this demand service to information and services that can also be carried out at internet. The operationalization of the research, with a descriptive character, at first, include a qualitative approach, to contextualize and specify the theme e-Gov and discern the context of your application as a tool for interaction with citizens by Federal Revenue, outlining through documentary analyze and interviews with technical of the agency. After, the research gets a quantitative approach, using the instruments to survey with users of services through the Internet and face-to-face support. The data analysis includes the linking of qualitative and quantitative approaches through concomitant triangulation, assessing constructs maturity, availability, ease of use, reliability and accessibility and clearness. The evidences point to that reliability and availability contribute directly to the effectiveness of the website. The ease of use, although to a lesser extent, can also be deployed as an attribute that affects positively, at least in the perception of users. The construct accessibility and transparency denotes the lowest valuation, and even though not affected directly the efficiency, demonstrates that this agency needs to deepen the e-Gov practices in this aspect. Maturity is the construct that limits the effectiveness and leads citizens to search face-to-face services. In general, the entries to the Federal Revenue as an importance in e-Gov in Brazil are confirmed, but there is a long way for the use of these tools to consolidate and produce the benefits from all its potentiality.